La literatura infantil y su incidencia pedagógica para el desarrollo del lenguaje oral en los niños y niñas de educación inicial de la unidad educativa particular mixta Principito y Marcel Laniado de Wind de la ciudad de Machala en el periodo lectivo 2012 - 2013. - Garcés Pizarro, Olga Pamela (2015)
This research aims to demonstrate and explain the benefits of children's reading and teaching resources in the exercise of teaching practice, and the improvement of the teaching-learning process. It is essential to incorporate the teaching resources in educational activities as these facilitate cognitive development of children / as, and allow to achieve better learning skills for educational institutions. As the process of learning a direct and active relationship between teachers and children / as, where teachers facilitate students in the assimilation of knowledge, guiding the teaching process in this way to obtain and assimilation of knowledge is imperative stimulation mind and capacities of children / as, this is achieved by incorporating elements of children's reading in improving oral language.